2012
DOI: 10.1088/0004-637x/749/2/112
|View full text |Cite
|
Sign up to set email alerts
|

A Transient Sub-Eddington Black Hole X-Ray Binary Candidate in the Dust Lanes of Centaurus A

Abstract: We report the discovery of a bright X-ray transient CXOU J132527.6−430023 in the nearby early-type galaxy NGC 5128. The source was first detected over the course of five Chandra observations in 2007, reaching an unabsorbed outburst luminosity of (1-2) × 10 38 erg s −1 in the 0.5-7.0 keV band before returning to quiescence. Such luminosities are possible for both stellar-mass black hole and neutron star (NS) X-ray binary transients. Here, we attempt to characterize the nature of the compact object. No counterpa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…This implies that the GUP-enhanced equation of state prevents gravitational collapse and halts the formation of compact astrophysical objects denser than white dwarfs. This prediction contradicts astronomical observations that confirm the existence of pulsars [79] and black holes [1012]. Moreover, it has been observed that the masses of white dwarfs fall well within the Chandrasekhar limit [1315],MnormalCh=2.01823π2(cG)3/21(μemu)25.76μe2M,apart from the super-Chandrasekhar white dwarfs, that may well be double-degenerate mergers [1618].…”
Section: Introductionmentioning
confidence: 98%
“…This implies that the GUP-enhanced equation of state prevents gravitational collapse and halts the formation of compact astrophysical objects denser than white dwarfs. This prediction contradicts astronomical observations that confirm the existence of pulsars [79] and black holes [1012]. Moreover, it has been observed that the masses of white dwarfs fall well within the Chandrasekhar limit [1315],MnormalCh=2.01823π2(cG)3/21(μemu)25.76μe2M,apart from the super-Chandrasekhar white dwarfs, that may well be double-degenerate mergers [1618].…”
Section: Introductionmentioning
confidence: 98%
“…Circular extraction regions were produced, centered on the chip position of each source, whether it is detected in an observation or not. As was the case for the work of Burke et al (2012), these regions had radius r p7 , equal to 90% of the 7 keV extraction radius at that chip position. We then excluded regions in the jet, radio lobe and nucleus from our source list.…”
Section: Source Detection and Alignmentmentioning
confidence: 70%
“…There is a large fall in flux from this source, the spectral counts falling to 29 in the final observation from over 1100 in the first; however, it is still above our detection limit. The low inner-disk temperature in the thermal state, combined with the high inter-observation variability, strongly suggests that this is a BH LMXB transient candidate, similar to S14 (Burke et al 2012). NS LMXBs at this luminosity, L x > 10 38 erg s −1 , typically have a much flatter spectral shape over the Chandra band.…”
Section: Dust Lane Sourcesmentioning
confidence: 86%
See 1 more Smart Citation
“…This implies that GUP-enhanced equation of state prevents gravitational collapse and halts the formation of compact astrophysical objects denser than white dwarfs. This prediction contradicts astronomical observations that confirm the existence of pulsars [6][7][8] and black holes [9][10][11]. Moreover, it has been observed that the masses of (non-magnetic) white dwarfs fall well within the Chandrasekhar limit [12][13][14],…”
Section: Introductionmentioning
confidence: 82%